TEACHING LISTENING STRATEGIES TO INCREASE STUDENTS’ LISTENING COMPREHENSION - Dwi Rahayu; Chusna Apriyanti (LPPM Press STKIP PGRI Pacitan, 2017)
This study is aimed to find out the strategies used by the lecturer in increasing students’ listening comprehension. The researchers used descriptive qualitative research design. The data were collected through observation and interview. The observation was implemented on the teaching listening class during May to June 2017. The respondents were the students of listening class STKIP PGRI PACITAN grade 1. Some students randomly were being inteviewed by the researchers. Besides, the data are also found by reading the theories related to listening skill. Finally, after having been collected, researchers reduce the data, displaying the data and elaborating the result and gaining the conclusion. The result shows that lecturer’ strategies in overcoming listening problems faced by students are implemented in these three stages: pre listening, while listening, and post-listening. Pre listening consists of explaining the purpose of listening, looking at visual aids, recognizing vocabularies of the listening text, activating background knowledge, activating topic knowledge, giving motivation to the students, and preparing good conducive situation. While listening consists of activities listening with visual, predicting the content of the listening text. listening for the gist (general understanding) or specific information, filling in blanks of a transcript of a passage with the words missing, sequencing, total physical response, detecting the differences between the passage and the general knowledge, matching items, following a route on a map and repeating the material recorded. While post listening consists of summarizing and reviewing to encourage discussion, giving extended responses, setting students to work in pair to create the dialogues based on the listening passage and peer teaching.